About the Seasons - McKay, Sindy (South San Francisco, CA Treasure Bay, 2000)
Explores the seasons through the changing weather patterns and the changing activities of both children and animals"-- back cover.
"Take turns reading with your beginning reader!"--Cover.
Keywords: Seasons; Seasons; Spanish and English